2021
DOI: 10.1016/j.btre.2021.e00607
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide identification, phylogeny, and synteny analysis of sox gene family in common carp (Cyprinus carpio)

Abstract: Highlights 27 SOX (high-mobility group HMG-box) genes were identified in the C. carp genome. SOX genes ranging from 3496 (SOX6) to 924bp (SOX17b) which coded with putative protein series from 307 to 509 amino acids. Gene ontology revealed SOX proteins maximum involvement is in metabolic process 49.796 %. Chromosomal location and synteny analysis display all SOX gene are located on different chromosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…A similar phenomenon of double copies of members of the SoxE subfamily has also been seen in other teleost, such as the large yellow croaker and spinyhead croaker [33,34]. However, Cyprinus carpio has more SoxE (including CySox8a, CySox8b, CySox8c, CySox8d, CySox9a, CySox9b, CySox9c, CySox9d, CySox10a, and CySox10b) compared with S. maximus and other aforementioned fsh, implying that C. carpio underwent additional genome duplication events during evolution (4R-WGD events) [14].…”
Section: Resultssupporting
confidence: 63%
“…A similar phenomenon of double copies of members of the SoxE subfamily has also been seen in other teleost, such as the large yellow croaker and spinyhead croaker [33,34]. However, Cyprinus carpio has more SoxE (including CySox8a, CySox8b, CySox8c, CySox8d, CySox9a, CySox9b, CySox9c, CySox9d, CySox10a, and CySox10b) compared with S. maximus and other aforementioned fsh, implying that C. carpio underwent additional genome duplication events during evolution (4R-WGD events) [14].…”
Section: Resultssupporting
confidence: 63%
“…As per earlier research, phylogenetic relationships are established between Omicron with other variants based on the distance matrix [ 36 ]. Using the UPGMA algorithm, the mapping of variable strains at different branches was generated per the rules of phylogenetic preparation [ 37 ]. This study established an inference that Omicron shares a monophyletic clade [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Members of the gjSOXs family underwent genome-wide screening and were determined based on bioinformatics tools [19]. Briefly, the protein sequence file of G. japonicus was retrieved from the NCBI database (GCF_001447785.1).…”
Section: Analysis Of Conserved Regions Of Gjsox9 and The Gjsox Familymentioning
confidence: 99%
“…Genome data provide valuable resources for identifying genes or gene families via genome-wide identification or characterization [19,20]. BLAST analyses indicated that SOX9 orthologs were present in almost all metazoans [21].…”
Section: Introductionmentioning
confidence: 99%